Biosensors and bioelectronics - Karunakaran, Chandran; Bhargava, Kalpana; Benjamin, Robson; ScienceDirect eBooks (Amsterdam : Elsevier, 2015)
Biosensors and Bioelectronics presents the rapidly evolving methodologies that are relevant to biosensors and bioelectronics fabrication and characterization. The book provides a comprehensive understanding of biosensor functionality, and is an interdisciplinary reference that includes a range of interwoven contributing subjects, including electrochemistry, nanoparticles, and conducting polymers. Authored by a team of bioinstrumentation experts, this book serves as a blueprint for performing advanced fabrication and characterization of sensor systems(u2014)arming readers with an application-based reference that enriches the implementation of the most advanced technologies in the field. Features descriptions of functionalized nanocomposite materials and carbon fibre electrode-based biosensors for field and in vivo applications Presents a range of interwoven contributing subjects, including electrochemistry, nanoparticles, and conducting polymers Includes more than 70 figures and illustrations that enhance key concepts and aid in retention Ideal reference for those studying bioreceptors, transducers, bioinstrumentation, nanomaterials, immunosensors, nanotubes, nanoparticles, and electrostatic interactions Authored by a collaborative team of scientists with more than 50 years of experienced in field research and instruction combined.
Online resource; title from PDF title page (Ebsco, viewed July 15, 2015).
Includes bibliographical references and index.
Elsevier
Keywords: Biosensors; Bioelectronics; HEALTH & FITNESS / Allied Health Services / Medical Technology; MEDICAL / Biotechnology; TECHNOLOGY & ENGINEERING / Biomedical; Bioelectronics; Biosensors; Biosensing Techniques -- instrumentation; Electronic books